2008
DOI: 10.1177/0363546508325670
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Chondrocyte Implantation of the Ankle

Abstract: Autologous chondrocyte implantation of the talus yields significant functional improvement; however, further investigation is necessary to determine the long-term structural and biomechanical properties of the repair tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 67 publications
2
86
0
2
Order By: Relevance
“…In comparison to the knee, few studies of periosteal-based ACI in the ankle joint report success rates varying from 81.2 % to 100 % [12][13][14][15][16]. In the longest follow-up found in literature, Giannini et al [17] accounted a series of ten patients (defect size 3.1 cm²) with a follow-up of ten years.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the knee, few studies of periosteal-based ACI in the ankle joint report success rates varying from 81.2 % to 100 % [12][13][14][15][16]. In the longest follow-up found in literature, Giannini et al [17] accounted a series of ten patients (defect size 3.1 cm²) with a follow-up of ten years.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, Nam et al 18 did not recommend autologous chondrocyte implantation as an initial treatment option because the investigations on talar lesions were preliminary. Giza et al 17 suggested that matrix-induced autologous chondrocyte implantation into articular defects of the talus is a reasonable revision treatment for osteochondral defects of the talus in patients who do not respond to an initial bone marrow stimulation technique.…”
Section: Discussionmentioning
confidence: 99%
“…At followup 7 years after his injury, the patient had a normal physical examination and excellent functional outcome scores using the AOFAS Ankle-Hindfoot, Ankle Activity, and Tegner Activity Level Scales. Although the Tegner Activity Level Scale initially was designed for outcomes assessment of patients with knee ligament injuries, it has been used to assess function after ankle injuries as well [13,14,17,28]. The score of 100 was the maximal for the AOFAS AnkleHindfoot Scale; the score of 8 on the Ankle Activity Score represents tennis at the ''top level -international elite, professional, national team, or first division'' [8]; and level 8 on the Tegner Activity Level Scale represents ''competitive sports such as racquetball or bandy, squash or badminton, track and field athletics, downhill skiing'' [26].…”
Section: Discussionmentioning
confidence: 99%